Physiological Response of Layers to Alternative Feeding Regimen of Calcium Source and Phosphorus Level - Ahmad, Hafiz Anwar; Balander, Richard J. (International Journal of Poultry Science, 2004)
An experiment was conducted to determine the effects of dietary calcium source, phosphorus level and the time of feeding on the physiological responses of laying hens pertaining to egg shell formation. Seventy-two Hyline W-36 hens were divided into three treatment groups. Treatment 1 was fed a commercial layer ration as morning and evening feed with limestone as the calcium source. Treatment 2 was fed the commercial ration in the morning, while the evening feed contained a normal calcium level with limestone as the calcium source, but a lower phosphorus level than Treatment 1. Treatment 3 feed contained normal calcium and phosphorus in the morning while Treatment 3 evening feed contained normal calcium, but low phosphorus. The calcium source for Treatment 3 was ½ limestone and ½ oyster shell. Blood was drawn for each post-oviposition hour from all three-treatment groups to collect 4 samples per hour. Oyster shell or the reduced phosphorus level in the layers` diet did not raise the plasma calcium level in Treatment 2 or 3 compared to Treatment 1 that had a significantly higher plasma calcium level. Reduced dietary phosphorus decreased plasma inorganic phosphorus in Treatment 3. Limestone alone with reduced phosphorus (Treatment 2) did not decrease plasma phosphorus. Reduced dietary phosphorus and/or calcium source appears to have affected blood levels of estradiol and progesterone. Eggshell quality can be improved by partial (½) replacement of the limestone with Oyster shell. Reduced phosphorus did not improve eggshell quality, however, it did help indirectly by reducing plasma inorganic phosphorus, the excess of which is otherwise detrimental to eggshell quality.